2013
DOI: 10.1016/j.cell.2013.04.049
|View full text |Cite
|
Sign up to set email alerts
|

Reshaping Antibody Diversity

Abstract: Summary Unlike humans or mice, some species have limited genome encoded combinatorial diversity potential, yet mount a robust antibody response. Cows are unusual in having exceptionally long CDR H3 loops and few V-regions, but the mechanism for creating diversity is not understood. Deep sequencing revealed that ultralong CDR H3s contain a remarkable complexity of cysteines, suggesting that disulfide-bonded mini-domains may arise during repertoire development. Indeed, crystal structures of two cow antibodies re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
404
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 198 publications
(415 citation statements)
references
References 49 publications
11
404
0
Order By: Relevance
“…BnAbs isolated from chronic infection have a number of unusual features that have been selected to cope with the glycan shield including much longer than average HCDR3 loops 1012 . HCDR3s in most vertebrates have restricted lengths that predominantly encode loops of 12–16 amino acids upon VDJ recombination 9,1315 . Therefore, in many species, relatively few antibody precursors can be affinity-matured to HIV bnAbs.…”
Section: Main Textmentioning
confidence: 99%
See 2 more Smart Citations
“…BnAbs isolated from chronic infection have a number of unusual features that have been selected to cope with the glycan shield including much longer than average HCDR3 loops 1012 . HCDR3s in most vertebrates have restricted lengths that predominantly encode loops of 12–16 amino acids upon VDJ recombination 9,1315 . Therefore, in many species, relatively few antibody precursors can be affinity-matured to HIV bnAbs.…”
Section: Main Textmentioning
confidence: 99%
“…Therefore, in many species, relatively few antibody precursors can be affinity-matured to HIV bnAbs. Cows, however, produce antibodies with HCDR3s that average ~26 amino acids in length with an ultralong subset (10–15% of the repertoire) that can be over 70 amino acids in length 46,8,9,16 . Previous work has shown that repeated immunization over multiple years with a non-well-ordered Env trimer in cows can lead to some neutralization breadth in the immunoglobulin-rich colostrum 1719 , although with relatively low potency.…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…Heavy chain camelid antibodies offer the potential for high-level production in conventional bacterial and yeast biofermentation which may lead to large-scale, relatively low-cost production [64]. In contrast, the length of bovine CDRH3 is highly variable and longer (up to 70 amino acids) than those in other species particularly compared to human [16,[65][66][67][68]. The antibodies with ultralong CDRH3 can comprise up to 10-15% of the entire bovine IgG repertoire ( Figure 2) [16].…”
Section: Bovine Cdrh3 Length Goes Beyond Expectationmentioning
confidence: 99%
“…However, recent immunization studies in llamas and cows have resulted in induction of BrNAbs. Induction of BrNAbs in these animals is highly informative, as the studies from past 2 decades revealed that the antibodies from these species have unique structure facilitating antibody-antigen interaction through the less accessible epitopes [15,16]. The cows, particularly, produce exceptionally long CDRH3 which could be potentially advantageous in vaccine research developments.…”
Section: Introductionmentioning
confidence: 99%